Skin cancers in renal transplant recipients - Bordea, C (2001)
This thesis investigates the incidence and epidemiological characteristics of skin cancers that have occurred in the Oxford Renal Transplant Centre over a period of 21 years, immune responses and cells associated with the immune response in immunosuppressed patients with and without skin cancer, non-immunosuppressed patients with skin cancers and matched controls, and the effect of HLA and TNF-ɑ polymorphisms on the risk of subsequent skin cancer after transplantation. The epidemiological study showed a higher incidence and risk of skin cancer after transplantation than previously reported from centres in Europe. The increase is highest for squamous cell carcinoma, the most prevalent tumour type. A detailed anatomical distribution for individual tumour type and gender is provided and risk factors and cumulative incidences are assessed. A possible association with the arterio-venous fistula side is not confirmed. Delayed type hypersensitivity (DTH) responses and non-specific inflammatory responses are investigated in a novel design study. The results suggest reduced DTH responses in renal transplant patients with skin cancer with comparable inflammatory responses. It also confirmed the increased skin dryness in renal transplant patients, possibly a side effect of their medication. Furthermore the number of Langerhans cells and morphology are assessed in the same groups of patients. Transplant patients appear to have Langerhans cells with fewer and shorter dendrites. However the number of Langerhans cells does not appear to be a good predictor of the risk of skin cancer. The association of genes of the MHC region and polymorphic alleles of the TNF-ɑ gene with the risk of skin cancer after transplantation was studied. An association with HLA B27 and the risk of basal cell carcinoma was found, but no association with the TNF-ɑ alleles investigated.